Leatherface [videorecording (DVD)] - Dorff, Stephen, 1973-; Taylor, Lili; Strike, Sam (Lions Gate Entertainment, 2017)
A teenage leatherface escapes from a mental hospital with three other inmates, kidnapping a young nurse and taking her on a road trip from hell, while being pursued by a lawman out for revenge.